Connectivism Theory in Education and Its Applications to Curriculum and Instruction - Peter, Joy Abosede; Ogunlade, Oyeronke O. (ASEAN Journal of Educational Research and Technology, 2024)
In an era characterized by rapid technological advancements and interconnectedness, traditional approaches to education are being reimagined. Connectivism is a theory of learning that combines information and communication technology to form a networked learning environment. This expository article addresses the connective theory and explores its applications to curriculum and instructional strategies, using a literature review approach. Connectivism's influence on curriculum design is profound, encouraging educators to revise learning experiences, because the increasing use of technology as an educational tool has changed the learning landscape. It also shapes instructional strategies that align with the digital age because Connectivism relies heavily on technology, so the first step to creating a connective classroom is to introduce more opportunities for digital learning. The combination of digital literacy and critical thinking skills is essential for students to develop the skills necessary to work and communicate effectively in a diverse and interconnected world. As educators seek to embrace connectivism and its applications in curriculum and instruction, it made some practical recommendations to effectively implement connectivism in educational settings: Ensure educators and students are proficient in using these tools to maximize their connective learning experience.